2019
DOI: 10.1002/ppul.24344
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing parenthood with cystic fibrosis: Reproductive health and parenting concerns in individuals with cystic fibrosis

Abstract: Background As life expectancy for cystic fibrosis (CF) has increased in recent decades, more individuals with CF are becoming parents. The objectives of this study were to describe the parenting and reproductive health concerns of individuals with CF and to identify the psychosocial and educational needs related to parenthood with CF. Methods Twenty adults with CF, including parents and non‐parents, participated in one‐on‐one, semi‐structured interviews about reproductive health and parenting. Questions pertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(74 citation statements)
references
References 25 publications
0
67
1
Order By: Relevance
“…A total of 2335 resources were screened with 31 resources meeting our eligibility criteria. Using the inclusion criteria presented in Figure 1, 10 articles (Barker et al, 2017; Bianco et al, 2019; Cammidge et al, 2016; Duguépéroux et al, 2006; Hailey et al, 2019; Jessup et al, 2018; Schechter et al, 2013; Ullrich et al, 2015a, 2015b, 2015c) and three abstracts were retained (Downey et al, 2015; Frankl and Hjelte, 2004; Lauritsen and Pressler, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2335 resources were screened with 31 resources meeting our eligibility criteria. Using the inclusion criteria presented in Figure 1, 10 articles (Barker et al, 2017; Bianco et al, 2019; Cammidge et al, 2016; Duguépéroux et al, 2006; Hailey et al, 2019; Jessup et al, 2018; Schechter et al, 2013; Ullrich et al, 2015a, 2015b, 2015c) and three abstracts were retained (Downey et al, 2015; Frankl and Hjelte, 2004; Lauritsen and Pressler, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies were European (Barker et al, 2017; Bianco et al, 2019; Cammidge et al, 2016; Downey et al, 2015; Duguépéroux et al, 2006; Frankl and Hjelte, 2004; Lauritsen and Pressler, 2008; Ullrich et al, 2015a, 2015b, 2015c), four studies were conducted in the United Kingdom (Barker et al, 2017; Bianco et al, 2019; Cammidge et al, 2016; Downey et al, 2015), and half used qualitative designs (Barker et al, 2017; Cammidge et al, 2016; Downey et al, 2015; Hailey et al, 2019; Jessup et al, 2018). Three articles described different parts of a larger study, using the same sample (Ullrich et al, 2015a, 2015b, 2015c) or a portion of the larger sample (Ullrich et al, 2015a, 2015b).…”
Section: Resultsmentioning
confidence: 99%
“…Published pregnancy guidelines are 12 years old [14] and need updating, particularly in the current era of CFTR modulators [15] . Data show that even well after their pregnancy is over, women with CF experience stresses relating to juggling their own needs and those of their children and required more clinic visits and courses of IV antibiotics when compared to matched controls, highlighting impacts on their physical and mental health of caring for small children [16,17] . Later in life, multiple studies on gender-based differences in health have reported poorer outcomes for females with CF [1,6,8] .…”
Section: Perceptions Of Gender-related Issues Affecting People With Cmentioning
confidence: 99%
“…The physiological challenges of pregnancy are also significant, and the risks, particularly in those with impaired lung function, should be fully discussed and explored, when possible, before embarking on pregnancy. 134,135 The subsequent challenges of raising a family. In addition, CF treatment programs usually require significant help from partners, parents, and other carers.…”
Section: Fertility and Pregnancymentioning
confidence: 99%
“…In the event of the partner being a carrier of CFTR mutation, preimplantation diagnosis is possible if the couple wishes to avoid having a child with CF. 134,135 Several women have had successful pregnancies while on treatment with CFTR modulators, with no reports of fetal abnormalities so far. 137…”
Section: Fertility and Pregnancymentioning
confidence: 99%